«Recruit», «soldier», «conscript»: about the social status of the person leaving for the army in russian villages - Chernysheva, Y.S. (Perm Federal Research Centre Journal, 2022)
The article examines the changes in the social status of a young man going into the army during the XX century. The attitude to service in the army has been changing throughout the XX century. At the same time, the fullness of the recrut ritual is transformed, and the attitude of the villagers to the young man leaving for the army is changing. The study provides for a synchronic examination of the public attitude to service in the army, the composition of the recruitment rite and the social status of those leaving for the army in several time periods: the end of the XIX – beginning of the XX centuries. (before 1917), 1920s–1930s and 60s–90s. XX century. The main sources were field ethnographic materials, published articles on recruitment rituals, pre-revolutionary periodicals. The analysis showed that conscripts were treated with respect at all times. The perception of draft dodgers is changing – if at the beginning of the century they were treated mostly indifferently, then by the end of the century service in the army is an integral stage of a young man’s life.